2020
DOI: 10.1155/2020/6989452
|View full text |Cite
|
Sign up to set email alerts
|

High-Capacity Reversible Data Hiding in Encrypted Images by Information Preprocessing

Abstract: With the development of cloud computing, high-capacity reversible data hiding in an encrypted image (RDHEI) has attracted increasing attention. The main idea of RDHEI is that an image owner encrypts a cover image, and then a data hider embeds secret information in the encrypted image. With the information hiding key, a receiver can extract the embedded data from the hidden image; with the encryption key, the receiver reconstructs the original image. In this paper, we can embed data in the form of random bits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Eight scanned documents of [26,33] were used as secret data. Table 4 lists eight pages of scanned documents.…”
Section: A Detailed Examplementioning
confidence: 99%
“…Eight scanned documents of [26,33] were used as secret data. Table 4 lists eight pages of scanned documents.…”
Section: A Detailed Examplementioning
confidence: 99%
“…The contribution of research work is as shown in:  Presented efficient data masking method that brings good tradeoffs between embedding capacity and reconstruction quality.  EDM method attain higher embedding capacity and higher quality recovery mesh and error-free extraction compared with the existing state-of-the-art data masking method [16].…”
Section: Introductionmentioning
confidence: 98%